Gut-Brain Psychology: Rethinking Psychology From the Microbiota–Gut–Brain Axis - Liang, Shan; Wu, Xiaoli; Jin, Feng (Frontiers in Integrative Neuroscience, 2018)
Mental disorders and neurological diseases have brought rapidly increasing medical burdens. Although extensive researches have been conducted hugely, effective therapies have been still progressing slowly. Current dilemma reminds us that the human is a superorganism. Only if we take the human self and its partner microbiota into consideration at the same time can we better understand these diseases. Over the last few centuries, the partner microbiota has experienced tremendous changes much more than human own genes because of modern transformations in diet, lifestyle, medical care, and so on, paralleling the modern epidemiological transition. Existing research indicates that gut microbiota plays an important role in this transition. According to gut–brain psychology, the gut microbiota is a crucial part of gut–brain, and it communicates with the brain via the microbiota–gut–brain axis. The gut microbiota almost develops synchronously with the gut–brain, brain, and mind. Gut microbiota influences various normal mental processes and mental phenomena and they are involved in the pathophysiology of numerous mental and neurological diseases. Targeting microbiota in therapy for these diseases is a promising approach that is supported by three theories: the gut microbiota hypothesis, the “old friend” hypothesis, and the leaky gut theory. The effects of gut microbiota in brain and behavior are fulfilled through the microbiota-gut-brain axis which is mainly composed of nervous pathway, endocrine pathway, and immune pathway. Undoubtedly, gut–brain psychology will bring great enhancement to psychology, neuroscience, and psychiatry. Various microbiota improving methods including FMT, probiotics, prebiotics, healthy diet, and healthy lifestyle have shown capability to promote the function of gut brain, microbiota-gut-brain axis and brain. Harnessing gut microbiota to improve brain and mental health, prevent and therapy related diseases will be true in the future.